Investigation of metal nanopowders by the method of electron microscopy - Ibraev, E.S.; Suyundykova, A.S.; Partizan, G.; Nakysbekov, Zh.T. (Recent Contributions to Physics, 2019)
This article presents the results of experiments on the study of metal nanopowders by the method of ultrahigh resolution scanning electron microscopy and transmission microscopy. Electron microscopy is one of the main methods of studying nanomaterials that allows you to directly see the objects under study. In a scanning electron microscope, secondary, reflected and absorbed electrons are used to obtain the image of the sample surface. The remaining emissions are used as additional sources of information. The results of scanning electron microscopy showed that nickel and iron nanoclusters are close to a spherical shape with an average diameter of 50 and 65 nm, respectively. The results of studies by transmission electron microscopy of NP of nickel and iron are consistent with the results obtained using ultrahigh resolution scanning electron microscopy. In contrast to NP of nickel and iron, the histogram of the size distribution of copper NP has a bimodal distribution. The average particle diameter of the first and second fraction is 23.6 and 81 nm, respectively. The results of scanning and transmission electron microscopy showed that copper nanoclusters have distinct crystallographic faces and edges.